Gerakan Santri di Situbondo: Telaah terhadap Gerakan Protes Kaum Santri PP. Salafiyah Syafi’iyah Sukorejo Asembagus dalam Menentang Korupsi Penguasa Daerah di Kabupaten Situbondo Jawa Timur: Santri Movement in Situbondo: A Study on the Protest Movement of Santri of PP. Salafiyah Syafi’iyah Sukorejo Asembagus in Opposing Local Government Corruption in Situbondo Regency, East Java - Imam Bonjol Jauhari (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2018)
Following the 1998 Reformation, democratic euphoria triggered waves of civil protests across Indonesia, including a santri-led movement opposing regional treasury corruption in Situbondo Regency. This study examines the causes and strategies of the protest movement conducted by santri from the Salafiyah Syafi'iyah Sukorejo Islamic boarding school against the corrupt practices of the Situbondo regent (2006–2007). Using a descriptive approach, data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman model. The findings reveal three main points. First, the roots of santri protest movements in Situbondo emerged during the New Order regime. Second, the emergence of this movement is inseparable from the influence of the student-led Reformation movement, pro-democracy activism, and post-1998 democratic euphoria. Third, the primary drivers were public disappointment over corruption, collusion, and nepotism (KKN), violations of socio-economic rights, and weak law enforcement. The movement employed strategies ranging from symbolic non-violent actions to the blockade of the Pantura highway, ultimately forcing the Corruption Eradication Commission (KPK) to investigate the case, resulting in a nine-year prison sentence for the regent. This study recommends strengthening civic participation and social movement literacy among local activists. Pascareformasi 1998, euforia demokrasi memicu gelombang protes sipil di berbagai daerah di Indonesia, termasuk gerakan santri yang menentang korupsi kas daerah di Kabupaten Situbondo. Penelitian ini mengkaji sebab-sebab munculnya serta strategi gerakan protes yang dilakukan oleh kaum santri Pondok Pesantren Salafiyah Syafi’iyah Sukorejo dalam melawan praktik korupsi yang dilakukan oleh Bupati Situbondo periode 2006-2007. Penelitian ini menggunakan pendekatan deskriptif dengan pengumpulan data melalui wawancara mendalam, observasi, dan studi dokumentasi. Analisis data mengikuti model Miles dan Huberman. Hasil penelitian menunjukkan bahwa pertama, akar gerakan protes santri telah ada sejak era Orde Baru. Kedua, kemunculan gerakan ini tidak terlepas dari pengaruh gerakan reformasi mahasiswa, gerakan pro-demokrasi, dan euphoria demokrasi pasca-1998. Ketiga, faktor pemicu utama adalah kekecewaan terhadap praktik korupsi, kolusi, dan nepotisme (KKN), pelanggaran hak sosial-ekonomi masyarakat, serta lemahnya penegakan hukum. Gerakan ini menggunakan strategi aksi simbolis non-kekerasan hingga pemblokadean jalur pantura, yang akhirnya memaksa KPK mengusut tuntas kasus tersebut dan menjatuhkan hukuman 9 tahun penjara kepada bupati. Penelitian ini merekomendasikan penguatan partisipasi sipil dan literasi gerakan sosial bagi aktivis lokal.